Load area aggregation considering integration of electric vehicles to the system (2015)
Current electric power systems have an increasing penetration of electric vehicles, and its effect has to be considered in different studies, such as optimal dispatch or voltage stability, among others. Additionally, considering that power system analysis becomes complex when the number of buses increase, this paper presents a methodology for aggregation of load areas that use a measurement-based load modeling approach based on an evolutionary computational technique and a classical reduction method. This aggregate load area model is proposed to reduce areas that consider electric vehicle (EV) load models. The proposed method provides a static equivalent load model and an equivalent network that can be used to reduce the computational effort required by power systemstudies. In order to validate the application of the proposed methodology, a 30-bus power system considering several disturbances and levels of penetration of the electric vehicles was used. The results show that the equivalent network model allows the reproduction of different events with an acceptable accuracy when it is compared to the original system behavior.